(untitled) (Research, Society and Development, 2022)
The linear economic model disseminated from the industrial evolution has generated an alert regarding the great use of natural resources, as they are becoming increasingly scarce. Then comes the need to create a new model, the Circular Economy, based on sustainable principles and which has remanufacturing as an important tool for the extension of product use cycles. The concept brought within the remanufacturing aims to mitigate the impacts of overproduction and high consumption through the disassembly, cleaning and repair of damaged parts, turning products that were in the process of disposal into products ready for new use, with guaranteed quality and functionality. This study aimed to carry out a bibliometric research, within the scientific bases Scopus and Web Of Science, and to identify the evolution of publications on remanufacturing within the context of the Circular Economy. Through this research, it was possible to demonstrate the evolution of the theme in the last five years, mainly in European countries and China. The number of publications practically doubled and it is possible to observe a tendency to relate the themes to areas of technology, such as Industry 4.0, Blockchain, Machine Learning, among others, which goes beyond the remodeling of the product design alone.